Підходи до нейромережевої ідентифікації та нейрокеруванням технічним процесом сушіння деревини - Петрянич, Олександр; Соколовський, Ярослав (Видавництво Національного університету «Львівська політехніка», 2009)
Now in theory and in practice widely used approaches to the identification model (algorithm and model) and the Neuro control process of drying wood in wood-drying chamber according to the conditions on the basis of the neural network/ We analized different methods of managing the process of drying wood and choose digital one. To digital control applies Neuro control which allows to take into account background and reduce the error results.
Keywords: wood drying; neuro control; Neuro - PID controller; temperature; humidity